Histologic differences between primary high myopia and secondary high myopia due to congenital glaucoma - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta ophthalmologica, 2016)
Purpose To search for histomorphometric differences between eyes with primary high myopia (PHM) or secondary high axial myopia (SHM) caused by congenital glaucoma, and non-highly myopic eyes (NHM). Methods Histologic anterior-posterior sections were histomorphometrically examined. Results The investigation included 58 human globes (mean age: 61.5 ± 18.5 years; axial length: 27.3 ± 4.0 mm; range: 21.0-39.0 mm). Bruch's membrane thickness was thinner in SHM than in PHM (posterior pole: p = 0.007; parapapillary region: p = 0.007); midpoint posterior pole/equator = 0.05) and thinner in SHM than in NHM (all p < 0.04), while PHM and NHM did not differ (all p > 0.50). Choroidal thickness did not differ (all p ≥ 0.40) at any measurement location between SHM and PHM, and was thinner (p < 0.05) in both myopic groups than in NHM. Posterior sclera was thinner (p < 0.001) in both myopic groups than in NHM, with no significant difference between both myopic groups. Pars plana scleral thickness was thinner (p = 0.02) in SHM than in PHM after adjusting for axial length. Scleral volume (p = 0.41) and choroidal volume (p = 0.74) did not differ between any of the groups. Conclusions Thinning of Bruch's membrane overall is typical for SHM while eyes with PHM have a normal Bruch's membrane thickness. It may point to Bruch's membrane as an active part in the process of emmetropization/myopization. SHM in contrast to PHM showed scleral thinning in the pars plana region suggesting that the process of emmetropization/myopization takes place posterior to the pars plana. Both SHM and PHM unspecifically showed an axial length associated with thinning of choroid and posterior sclera, while both myopic groups did not differ with NHM in choroidal and scleral volume.